Baif Characteristics Wave And Optics To Train Science Literacy Ability By Rvgm Of Junior High School Students - Azimatun Ni’mah Hasan; I Ketut Mahardika; Yushardi Yushardi (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2017)
This article describes BAIF characteristics (physics textbook) to train science literacy ability through VGM representation of junior high school students. The aim of the research is how BAIF characteristics to train science literacy ability through VGM representation of junior high school students. The aim of research can be described as two problems. First, is BAIF consist of the example of application refer to science literacy ability? Second, how is the BAIF writing pattern for junior high school students? Type of this research is R & D (Research and Development). The research is started by collecting qualitative data, and then arranging draft of BAIF until to be BAIF which ready to validation. The subject of research is BAIF to train science literacy ability through VGM representation of junior high school students. The respondents of research are students of an 8th-grade junior high school in the even semester. The technique of collecting data is observation, questionnaire, test, and document. The result of the research shows that BAIF characteristics has been consisting the example of application to train science literacy ability through VGM, and has a pattern of writing order such as title, a title of sub topic, material feature, the example of exercise item, exercise item as competence test, and references.